Ordning och reda i ordspråksförrådet? Om struktur och innehåll i Grubbs Penu proverbiale (1665) - Skjöldberg, Emma (Nordiske Studier i Leksikografi, 2010)
This paper reports on a study of the first exhaustive Swedish dictionary of multiword expressions, Penu proverbiale, which was compiled by Christopher L. Grubb in the middle of the 17th century. The book includes a lemma list of more than 3,900 expressions, especially proverbs. In the paper, I focus on the sections with expressions beginning with the letters D and P. Almost all the expressions are provided with semantic descriptions. Many of the proverbs are also related to other synonymous Swedish proverbs. Furthermore, the proverbs in the lemma list are connected to synonymous expressions in Latin and German and to Bible passages. The dictionary by Grubb is very well structured and provides the user with sets of phrases expressing the same idea, which of course is very useful in production.